Cost estimation techniques for web projects - Mendes, Emilia (IGI Pub., 2008)
"This book provides a step-by-step methodology to improving cost estimation practices for Web projects. Utilizing such techniques as stepwise regression modeling, case-base reasoning, classification and regression trees, and expert opinion, it is a powerful tool for scholars, researchers, and practitioners in the areas of Web development, Web engineering, project management, and software engineering"--Provided by publisher